2016
DOI: 10.5217/ir.2016.14.4.297
|View full text |Cite
|
Sign up to set email alerts
|

Irritable bowel syndrome and inflammatory bowel disease overlap syndrome: pieces of the puzzle are falling into place

Abstract: Irritable bowel syndrome (IBS), a common gastrointestinal disorder involving the gut-brain axis, and inflammatory bowel disease (IBD), a chronic relapsing inflammatory disorder, are both increasing in incidence and prevalence in Asia. Both have significant overlap in terms of symptoms, pathophysiology, and treatment, suggesting the possibility of IBS and IBD being a single disease entity albeit at opposite ends of the spectrum. We examined the similarities and differences in IBS and IBD, and offer new thoughts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 65 publications
0
23
0
8
Order By: Relevance
“…Both reflect MT-associated immune activation ( Monnig et al, 2016 ). Previous studies have reported that MT is an exclusive pathogenic characteristics in IBD/IBS ( Abdul et al, 2016 ), graft-versus-host disease ( Eriguchi et al, 2012 ) and HIV disease ( Yim et al, 2009 ), which feature increased levels of LPS-sCD14 and EndoCAb-IgM. Indeed, the commensal flora operate synergistically with the intestinal barrier, and interact with the innate immune system well.…”
Section: Discussionmentioning
confidence: 99%
“…Both reflect MT-associated immune activation ( Monnig et al, 2016 ). Previous studies have reported that MT is an exclusive pathogenic characteristics in IBD/IBS ( Abdul et al, 2016 ), graft-versus-host disease ( Eriguchi et al, 2012 ) and HIV disease ( Yim et al, 2009 ), which feature increased levels of LPS-sCD14 and EndoCAb-IgM. Indeed, the commensal flora operate synergistically with the intestinal barrier, and interact with the innate immune system well.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, IBS was considered completely different from IBD; however, recent studies have suggested that some overlap may exist between these two disease entities [ 17 ]. Although the degrees of inflammation and visceral hypersensitivity between IBD and IBS are different, they have similarities regarding the brain-gut axis, some genetic factors, dysbiosis, and impaired epithelial barrier function [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology of IBS is not completely understood; however, dysregulation of the brain-gut axis is believed to lead to IBS [3]. Various central and peripheral mechanisms are indicated to be involved, such as altered GI motility, visceral hypersensitivity, alternation in the intestinal microbiota, low-grade immune activation, and intestinal inflammation, which may be linked to enhanced exposure to antigens due to increased intestinal permeability [3-7]. Therefore, IBS is a very heterogeneous disorder and can be subtyped based on the bowel habits of the patients, such as diarrhea or constipation [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, IBS is a very heterogeneous disorder and can be subtyped based on the bowel habits of the patients, such as diarrhea or constipation [8]. Furthermore, some of the organic mechanisms of IBS are partly shared with the pathophysiology of IBD, and similarities in clinical manifestations are also observed between IBS and IBD [3,9]. Postinfectious IBS (PI-IBS), which is diagnosed on the basis of acute onset of symptoms meeting the diagnostic criteria for IBS, has been regarded as a typical condition resulting from intestinal inflammation accompanied by other various pathophysiologic mechanisms [10].…”
Section: Introductionmentioning
confidence: 99%